Effect of Diabetic Foot Ulcer Prevention Education on the Knowledge, Attitude, and Practices of PKK Cadres in Suruh Kalang, Karanganyar - Endah Sri Wahyuni; Mike Chelsea Maharani; Karisma Dian Rahmawati (Jurnal Ilmiah Kesehatan, 2026)
Diabetic foot ulcers are characterized by a disruption of skin integrity or infection that may extend to subcutaneous tissue, muscles, tendons, or bone. In Indonesia, the prevalence of diabetic foot ulcers is approximately 15%, with amputation rates of around 30% and mortality rates reaching up to 32%. One key strategy for preventing diabetic foot ulcers is health promotion conducted by community health cadres, who serve as frontline agents in public health initiatives. Preventive efforts include proper foot care practices and the implementation of diabetic foot exercises. The knowledge, attitudes, and behaviours of healthcare cadres play a crucial role in the success of both preventive and promotive interventions. Adequate knowledge supports the formation of positive attitudes, which subsequently encourage appropriate health behaviours. Structured educational programs that incorporate lectures, group discussions, demonstrations, and pre- and post-intervention evaluations are effective in improving the knowledge, attitudes, and behaviours of health cadres. Evidence from such interventions demonstrates a statistically significant improvement in these domains (p-value = 0.000). Therefore, the implementation of a sustainable and continuous education program is essential to strengthen diabetic foot ulcer prevention efforts by health cadres within the community and to ultimately reduce the incidence of diabetic foot ulcers